Memori Kolektif dan Teologi Luka: Kearifan Lokal sebagai Jalan Pemulihan Trauma Sosial - Boby Andika Sinaga; Toman Mardohar Mauliate Tambunan (PT. Penerbit Tiga Mutiara, 2025)
This study develops an interdisciplinary theological framework that integrates collective memory, a theology of woundedness, and local wisdom as epistemological and pastoral strategies for engaging with social trauma inscribed in the communal body of postcolonial and post-conflict societies in Indonesia. Collective memory, as examined by Halbwachs, Assmann, and Volf, is not construed as a mere aggregation of historical facts but as a cultural construction that shapes theological identity through performative, ritualistic, and narrative social processes. The theology of woundedness, informed by the works of Rambo, Moltmann, Jones, and Brock, resists binary categorizations between suffering and salvation, positioning wounds instead as loci theologici—revelatory spaces wherein the Holy Spirit dwells amidst unhealed wounds as a manifestation of divine solidarity and the possibility of redemption. Employing a qualitative-descriptive methodological framework and contextual hermeneutics, this research investigates local narratives, healing rituals, customary symbols, and inculturated liturgies among Christian communities in Ambon, Poso, and East Nusa Tenggara. The findings suggest that local wisdom functions not merely as a cultural instrument but also as a sacramental medium through which the Spirit operates incarnationally. The integration of these three dimensions demonstrates that post-traumatic restoration cannot be reduced to psychological or therapeutic pastoral practices alone; rather, it demands a theologically transformative, contextually rooted, and dialogical articulation of the wounded social body. Within this construct, the Church is envisioned as an anamnetic community that employs collective memory as a praxis of salvation, regards local culture as a spiritual body, and embraces woundedness as a participatory locus within the salvific narrative. Accordingly, this study contributes a novel paradigm for contextual theology and pastoral praxis in multicultural societies marked by the legacy of historical suffering and the urgent need for reconciliation grounded in justice and memory.